Kampung Beting: Family Resilience Against Religious Radicalism - Suhardiman, Suhardiman; Ar., Eka Hendry; Nizar, Muhammad (Al-Albab, 2023)
The work cuptures the rise of terrorist movements involving families. The studies of family involvement in acts of terrorism in Indonesia have not much been done. The work is based on research conducted in Kampung Beting of Pontianak City, which is stigmatized as a drug trafficking village. It explores family parenting patterns and family responses to live problems especially on community literacy about religious radicalism. The findings include, first, the pattern of instilling religious values in families is relatively vulnerable. Family parentings have shown physical resilience, social resilience and psychological resilience. The work finds the important roles of parents in instilling religious values and building communication with their children and the ability of families to solve problems they face. Education has been found very important within the community. Second, with regard to the existing conditions, people choose to “make peace” with the reality. The attitude of the people is split from pessimistic, pragmatic and optimistic. Third, public literacy about religious radicalism is quite good among ordinary people and religious and community leaders. Being radical in society’s point of view is an act of violence, while adhering to religious principles is considered not being radical. Defending the honor of religion is a matter of principle, thus encouraging them to fight. Fourth, four factors fortifying the community include the open and straightforward attitude of the community, the community involvement into the city security network, the high community mechanical solidarity and the effective role of religious leaders in fostering society.